Схеми модуляції для систем стільникового зв’язку 5G - Петрачков, М. О. (ХНУРЕ, 2023)
The choice of a specific type of modulation depends on such characteristics of the communication system as bandwidth, noise immunity, capacity. Various types of modulation based on subband filtering, pulse shaping, and precoding to reduce out-of-band interference have been proposed to enable communication networks to meet the requirements of 5G networks. This work is devoted to an overview of the main types of modulation for 5G systems